Strengthening the Deposit Insurance Corporation (LPS) with Authority as the Executor of the Restructuring Program (PRP) - Novira, Elyana (JURNAL AKTA, 2024)
Public trust in banking is an important foundation for maintaining financial system stability. The formation of the Deposit Insurance Corporation (LPS) in Indonesia aims to protect customer funds and ensure the banking system's stability. This research aims to evaluate the effectiveness of LPS authority in implementing the Banking Restructuring Program (PRP) as mandated by Law No. 9 of 2016. The method used is descriptive analysis with a qualitative approach based on literature review and secondary data, including related regulations, the role of LPS in Indonesia, and comparisons with similar institutions in other countries. The research results show that LPS's authority, such as taking over problematic bank assets, providing liquidity, and implementing restructuring, has increased financial stability. However, challenges in the form of moral hazard are still the main issue. In addition, the success of LPS is highly dependent on the support of a strong legal framework and cooperation between financial institutions. In conclusion, strengthening LPS in implementing PRP can be an effective financial stabilization model, but it requires strict supervision to minimize negative impacts. The implications of this research highlight the importance of integrated policies between the government and the banking sector in facing potential crises in the future